Assessing the health-state utility values of rare disease-hemophilia B using EQ-5D-5L: a study based on the Chinese population - Chuchuan Wan; Haotao Li; Yulin Zhang; Qiqi Wang; Yiwen Huang; Tao Guan; Xiaoyu Xi (Orphanet Journal of Rare Diseases)
Abstract Background Obtaining health-state utility values (HSUVs) aids in making scientific decisions in patient health management, especially for rare disease patients. However, there is currently no research specifically measuring the HSUVs of Chinese hemophilia B patients. Therefore, this study aims to assess the HSUVs of hemophilia B patients in China and explore its potential influencing factors. Methods The sociodemographic characteristics of patients were obtained from the Beijing Hemophilia Home Care Center (BHHCC) database. And the HSUVs were further obtained by reaching hemophilia B patients through an application of BHHCC and the Chinese version of the EQ-5D-5L. The beta regression model was used to explore the potential influencing factors of the HSUVs of patients. Results A total of 167 male patients (hemophilia B is an X-chromosome recessive disorder and female patients are rare) were included in the study. The mean age, HSUV and EQ-VAS were 20.01 ± 15.83, 0.755 ± 0.291 and 71.7 ± 22.7, respectively. The ceiling effects was 29.24%, and patients were more likely to experience problems in Pain/discomfort (57.49%). Compared to self-completion, proxy may overestimate HSUVs of patients. Pain (p < 0.000), disability (p < 0.000), complications (p < 0.001), inhibitors (p < 0.01), drug usage (p < 0.001), and bleeds (p < 0.000) were significantly associated with HSUVs in Chinese hemophilia B patients. Conclusions This study first assessed the HSUVs of Chinese hemophilia B patients, which provides support for further economic studies. Potential factors that affect the HSUVs of Chinese hemophilia B patients were also explored, which can provide a reference for developing health management measures. However, to enact more comprehensive and reliable disease management decisions, the effects of self-completion and proxy on the HSUVs of hemophilia B patients in China need to be further explored as well as the effects of specific factors.